Changes in prevalence of, and risk factors for, lameness in random samples of English sheep flocks: 2004-2013 - Winter, J.R.; Kaler, Jasmeet; Ferguson, Eamonn; KilBride, Amy L.; Green, Laura E. (Elsevier, 2015)
The aims of this study were to update the prevalence of lameness in sheep in England and identify novel risk factors. A total of 1260 sheep farmers responded to a postal survey. The survey captured detailed information on the period prevalence of lameness from May 2012 - April 2013 and the prevalence and farmer naming of lesions attributable to interdigital dermatitis (ID), severe footrot (SFR), contagious ovine digital dermatitis (CODD) and shelly hoof (SH), management and treatment of lameness, and farm and flock details. The global mean period prevalence of lameness fell between 2004 and 2013 from 10.6% to 4.9% and the geometric mean period prevalence of lameness fell from 5.4% (95% CL: 4.7-6.0%) to 3.5% (95% CI: 3.3%-3.7%). In 2013, more farmers were using vaccination and antibiotic treatment for ID and SFR and fewer farmers were using foot trimming as a routine or in therapeutic treatment than in 2004. Two over-dispersed Poisson regression models were developed with the outcome the period prevalence of lameness, one investigated associations with farmer estimates of prevalence of the four foot lesions and one investigated associations with management practices to control and treat lameness and footrot. A prevalence of ID >10%, SFR >2.5% and CODD >2.5% were associated with a higher prevalence of lameness compared with those lesions being absent, however, the prevalence of SH was not associated with a change in risk of lameness. A key novel management risk associated with higher prevalence of lameness was the rate of feet bleeding / 100 ewes trimmed / year. In addition, vaccination of ewes once per year and selecting breeding replacements from never-lame ewes were associated with a decreased risk of lameness. Other factors identified as associated with a lower risk of lameness for the first time in a random sample of farmers and a full risk model were: recognising lameness in sheep at locomotion score 1 compared with higher scores, treatment of the first lame sheep in a group compared with waiting until >5 were lame, treatment of lame sheep within 3 days, ease of catching lame sheep and quarantine for >21 days. A previously known factor associated with a lower risk of lameness was footbathing to prevent ID. We conclude that the prevalence of lameness in sheep in England has fallen and that this might be in part because of increased uptake of managements previously reported as beneficial to control lameness. Routine foot trimming should be avoided.